Otitis Media Complications: Labyrinthitis - Fajry Nurhadi (Rifa'Institute, 2022)
Background: Otitis media is an inflammation of part or all of the middle ear mucosa, eustachian tube, mastoid antrum and mastoid cells. Otitis media has many complications, one of which is extra-cranial complications such as labyrinthitis. Objective: To know more about labyrithitis and how to treat patients with labyrinthitis in otitis media. Method: This article was written using various sources from scientific journals and medical e-books. Source searches are carried out on the online portal of journal publications such as pdf drive, National Centre for Biotechnology Information/NCBI. Result and Discussion: Labyrinthitis is an inflammatory condition that occurs in the membranous labyrinth of the inner ear which is usually accompanied by vertigo, nausea, vomiting, tinnitus, and hearing loss to hearing loss. Treatment of labyrinthitis caused by viral in outpatients can be done by meeting fluid needs and adequate rest. In labyrinthitis caused by bacteria, topical antibiotic drops should be prescribed. Conclusion: Labyrinthitis is an inflammatory condition that occurs in the membranous labyrinth of the inner ear. Patients with labyrinthitis are usually accompanied by vertigo, nausea, vomiting, tinnitus, and hearing loss to hearing loss. The causes themselves are very diverse, such as viruses, bacteria, autoimmune, and even syphilis.